A quaternary ammonium salt glycogen, composite antibacterial hydrogel and preparation method and application thereof
By aminating and quaternary ammonium saltizing glycogen with dendritic nanosphere structure and crosslinking with gelatin, a quaternary ammonium salted glycogen-gelatin composite hydrogel was prepared, which solved the problems of poor antibacterial effects and poor biocompatibility of existing antibacterial hydrogels, and achieved efficient and low-toxic antibacterial effects.
Patent Information
- Application Number
- CN202310191365.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-28
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-02-28
AI Technical Summary
Existing natural polymer antibacterial hydrogels or hydrogels loaded with antibacterial agents have problems such as poor antibacterial effect, poor biocompatibility, poor mechanical properties, poor degradation performance, and drug resistance.
The glycogen with a unique dendritic nanosphere structure is used as raw material, and quaternary ammonium salted glycogen is formed through aminoation and quaternary ammonium salted glycogen, and then cross-linked with gelatin to prepare a quaternary ammonium salted glycogen-gelatin complex antibacterial hydrogel.
This composite hydrogel has the characteristics of high efficiency, low toxicity, drug resistance and low environmental impact. It can significantly inhibit Staphylococcus aureus and E. coli, and has good biocompatibility and low cytotoxicity.
Smart Images

Figure CN116178587B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a quaternary ammonium salt glycogen, a composite antibacterial hydrogel and a preparation method and application thereof, and belongs to the technical field of biomaterials. Background Art
[0002] Wound infection is a common adverse phenomenon in the medical field. It can cause local pain and wound inflammation at the mildest level, amputation, septic shock, and even life-threatening at the worst. Therefore, it is very necessary to treat the wound surface in a timely and effective manner before or during wound infection. Antibacterial hydrogels usually use physical embedding or chemical grafting to make the hydrogels antibacterial, which opens up new ideas for antibacterial treatment of wounds; however, there are also shortcomings such as drug resistance, heavy metal residues, and slow bactericidal effects. Summary of the invention
[0003] [Technical issues]
[0004] The natural polymer antibacterial hydrogels or hydrogels loaded with antibacterial agents commonly used in the prior art have problems such as poor antibacterial effect, poor biocompatibility, poor mechanical properties, poor degradation performance, and drug resistance.
[0005] [Technical solution]
[0006] In view of the above technical problems, the present invention provides a novel quaternized glycogen-gelatin composite antibacterial hydrogel and a preparation method thereof. The composite antibacterial hydrogel uses natural biological materials as a base material, comprehensively exerts the advantages of various materials, and has the characteristics of high efficiency antibacterial, low toxicity, drug resistance and small environmental impact. Specifically, glycogen with a unique dendritic nanosphere structure is used as a raw material, firstly an amino treatment is performed on its unique dendritic branched structure, and then partially quaternized by adjusting the reaction conditions, and finally the partially quaternized glycogen is cross-linked with gelatin to finally form a composite hydrogel with low toxicity and good antibacterial performance.
[0007] Glycogen is a natural dendritic macromolecular polysaccharide formed by the polymerization of glucose. It has dense branches and is rich in functional groups. It is a reserve polysaccharide of mammals and is mainly found in the liver and skeletal muscle of mammals. As an endogenous polysaccharide, glycogen is non-toxic and non-immunogenic. At the same time, glycogen can be degraded into glucose by amylase and glycosidase in the body.
[0008] Antimicrobial polymers are a class of materials that can kill microorganisms or inhibit their growth. They have the advantages of high efficiency, low toxicity, drug resistance, and low environmental impact, and are good substitutes for traditional small molecule antibiotics. Among them, cationic macromolecules and their hydrogel materials can adsorb negatively charged bacteria and cause bacterial death by destroying the cell structure. This unique bacterial membrane destruction mechanism not only makes it highly effective in killing bacteria, but also prevents bacteria from developing drug resistance.
[0009] The first object of the present invention is to provide a method for preparing a composite antibacterial hydrogel precursor quaternary ammonium salt glycogen, the method comprising the following steps:
[0010] (1) Synthesis of aminoglycogen
[0011] Dissolve glycogen in dimethyl sulfoxide, then add N,N-carbonyldiimidazole to activate at 35-40°C for 1-2 hours to obtain a reaction solution; then dissolve ethylenediamine in dimethyl sulfoxide to form an ethylenediamine solution; under nitrogen protection, slowly add the ethylenediamine solution to the reaction solution through a syringe, and react at room temperature for 18-24 hours; after the reaction, dialyze and freeze-dry to obtain amino glycogen;
[0012] (2) Synthesis of quaternary ammonium glycogen
[0013] The aminated glycogen prepared in step (1) is dissolved in deionized water, and the pH is adjusted to 8-9 with a NaOH solution to obtain an aminated glycogen solution; a quaternary ammonium salt is added to the aminated glycogen solution, and the solution is stirred at a constant temperature of 50-60° C. to react. After the reaction is completed, the solution is dialyzed and freeze-dried to obtain quaternary ammonium salt glycogen.
[0014] In one embodiment, the mass concentration of glycogen in the solution formed by dissolving glycogen in dimethyl sulfoxide in step (1) is 2-5%.
[0015] In one embodiment, the mass concentration of N,N-carbonyldiimidazole in the reaction solution of step (1) is 2-5%.
[0016] In one embodiment, the mass ratio of the quaternary ammonium salt to the aminoglycogen in step (2) is 1 to 5:2, preferably 2 to 3:2.
[0017] In one embodiment, the quaternary ammonium salt in step (2) includes one or more of 2,3-epoxypropyltrimethylammonium chloride, tributylmethylammonium chloride, dodecyltrimethylammonium chloride, and hexadecyltrimethylammonium bromide.
[0018] The second object of the present invention is to provide a quaternary ammonium salt glycogen prepared by the above method.
[0019] The third object of the present invention is to provide a use of the quaternary ammonium salt glycogen described above in the preparation of a composite hydrogel.
[0020] The fourth object of the present invention is to provide a method for preparing a quaternary ammonium salt glycogen-gelatin composite antibacterial hydrogel, the method comprising:
[0021] Gelatin and the quaternary ammonium glycogen described above are dissolved in ultrapure water at a mass ratio of 10:2-5, mixed evenly, and bubbles are removed. Then, the mixture is poured into a mold and refrigerated at 0-4°C for forming. Then, the formed gel is transferred into a crosslinker solution for immersion to perform a crosslinking reaction. The crosslinked gel is transferred into a PBS solution, immersed overnight, and washed to obtain a quaternary ammonium glycogen-gelatin composite hydrogel.
[0022] In one embodiment, the degassing is performed by removing bubbles from the mixed solution by ultrasound or centrifugation.
[0023] In one embodiment, the cross-linking agent solution includes one or more of EDC / NHS, genipin, or glutaraldehyde solution.
[0024] In one embodiment, the EDC concentration in the EDC / NHS solution is 1-3 mg / mL, the NHS concentration is 0.3-0.9 mg / mL, and the molar ratio of EDC:NHS is 2:1.
[0025] In one embodiment, the pH of the cross-linking agent solution is 4 to 6; and the cross-linking reaction time is 24 to 36 hours.
[0026] In one embodiment, the pH of the PBS solution is 6-8.
[0027] The fifth object of the present invention is to provide a quaternary ammonium salt glycogen-gelatin composite antibacterial hydrogel prepared by the above method.
[0028] The sixth object of the present invention is to provide an application of the above-mentioned quaternary ammonium salt glycogen-gelatin composite antibacterial hydrogel in the preparation of pharmaceutical products.
[0029] [Beneficial Effects]
[0030] The advantages of the preparation of the quaternary ammonium salt glycogen-gelatin composite antibacterial hydrogel of the present invention compared with the prior art are as follows:
[0031] (1) The present invention uses gelatin as a base material and constructs a glycogen derivative-gelatin composite hydrogel through amide bond chemical crosslinking. Compared with simple gelatin hydrogel, the addition of glycogen derivatives increases the crosslinking degree and mechanical strength of the gel system, slows down the degradation rate of the gel system, and improves the stability of the gel.
[0032] (2) The present invention uses glycogen with a unique dendritic nanosphere structure as a raw material, and performs step-by-step chemical modification on the glycogen, first amination and then quaternization; the amination process modifies the amino group to the dendritic branch of the glycogen, so that the chemical modification characteristics of the glycogen are improved, and at the same time, the glycogen is endowed with the ability to form amide bonds; the aminated glycogen is further quaternized to carry a large amount of positive charge to form a cationic dendritic macromolecular structure; the cationic dendritic macromolecule can change the permeability of the bacterial cell membrane, and the positively charged glycogen dendritic nanoparticles are combined with gelatin to form a hydrogel with antibacterial properties. The quaternized glycogen-gelatin composite hydrogel has a particularly prominent inhibitory effect on Staphylococcus aureus, and also shows a significant inhibitory effect on Escherichia coli. In addition, the quaternized glycogen-gelatin composite hydrogel is non-hemolytic and has low cytotoxicity and good biocompatibility.
[0033] (3) The quaternary ammonium salt glycogen-gelatin composite hydrogel of the present invention uses natural biomaterials as the base material, comprehensively exerts the advantages of various materials, and has the characteristics of high efficiency, low toxicity, drug resistance, and small environmental impact. It can become a new type of antibacterial wound dressing for preventing wound infection or repairing wounds after infection. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The actual pictures of the freeze-dried products of glycogen derivatives prepared in Example 1 of the present invention; (A) amino glycogen, (B) quaternary ammonium salt glycogen;
[0035] Figure 2 The infrared spectrum and nuclear magnetic resonance spectrum of the glycogen derivative prepared in Example 1 of the present invention;
[0036] Figure 3 This is a transmission electron microscopy image of the glycogen derivative prepared in Example 1 of the present invention;
[0037] Figure 4 The appearance morphology of the hydrogels prepared in Example 3 of the present invention and Comparative Examples 1 and 2;
[0038] Figure 5 The physicochemical properties data of the hydrogels prepared in Example 3 of the present invention and Comparative Examples 1 and 2 are shown in Figure 2; (A) compressive stress-strain curve; (B) swelling curve; (C) degradation rate in PBS solution;
[0039] Figure 6 This is a scanning electron microscope image of the quaternary ammonium salt glycogen-gelatin composite hydrogel prepared in Example 3 of the present invention;
[0040] Figure 7 The antibacterial rate data graph of the hydrogel prepared in Examples 3 and 4 of the present invention and Comparative Example 2;
[0041] Figure 8The data diagrams of cell experiment and hemolysis experiment of the hydrogel prepared in Example 3 of the present invention and Comparative Example 2; (A) cell survival rate; (B) hemolysis rate;
[0042] Fig. 9 The present invention is a flow chart for preparing the quaternary ammonium salt glycogen-gelatin composite hydrogel. DETAILED DESCRIPTION
[0043] The present invention is further described below in conjunction with embodiments but is not limited to the present invention.
[0044] The present invention calculates the degree of substitution according to the following formula:
[0045] 1. Determination of degree of substitution of aminoglycogen
[0046] The acid-base titration method was used to monitor the pH value of the mixed solution in real time as the titration volume of NaOH changed, and a titration curve of the NaOH solution volume and pH value change was drawn to determine the consumption of NaOH at two pH mutation points. The degree of substitution of amino glycogen was calculated according to the following formula.
[0047]
[0048] Where, DS: degree of substitution; W: mass of amino glycogen, g; C NaOH : NaOH solution concentration, mol / L; V1 and V2 are the NaOH consumption at two mutation points, L; M 葡萄糖单体 : Molecular weight of glucose monomer, 161 g / mol; M 乙二胺基 : The sum of the molecular weights of ethylenediamine and carbonyl, 87 g / mol.
[0049] 2. Determination of degree of substitution of quaternary ammonium salt glycogen
[0050] The degree of substitution of quaternary ammonium glycogen is determined by titration, with potassium chromate as the indicator and silver nitrate as the titration solution. After the silver ions fully react with the chloride ions in the quaternary ammonium glycogen, a brick-red precipitate is generated. By monitoring the amount of silver nitrate consumed, the degree of substitution of quaternary ammonium glycogen is estimated using the following formula.
[0051]
[0052] Where, DS: degree of substitution; V AgNO3 : Volume of silver nitrate consumed in titration, L; C AgNO3 : concentration of silver nitrate solution, mol / L; W: mass of quaternary ammonium salt glycogen, g; M 葡萄糖单体 : Molecular weight of glucose monomer, 161 g / mol; M 季铵盐 : Molecular weight of 2,3-epoxypropyltrimethylammonium chloride, 152 g / mol; M 乙二胺基: The sum of the molecular weights of ethylenediamine and carbonyl, 87 g / mol.
[0053] In the EDC / NHS solution involved in the present invention, EDC is 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and NHS is N-hydroxysuccinimide.
[0054] Example 1
[0055] The synthetic route of the quaternary ammonium salt glycogen of the present invention is as follows:
[0056]
[0057] (1) Synthesis of aminoglycogen
[0058] Weigh 2.0 g of glycogen and dissolve it in 100 mL of anhydrous dimethyl sulfoxide, and stir it magnetically until the glycogen is completely dissolved; then add 2.0 g of N,N-carbonyldiimidazole to the solution, and stir it at 35°C for 1 hour to fully activate it to obtain a reaction solution;
[0059] 3.08 mL of ethylenediamine was dissolved in 5 mL of dimethyl sulfoxide to form an ethylenediamine solution; then, the ethylenediamine solution was slowly added dropwise to the reaction solution through a syringe under nitrogen protection, and the reaction was carried out at room temperature for 24 hours; after the reaction was completed, the reaction solution was dialyzed for 3 days, and then the dialyzate was freeze-dried to obtain an amino glycogen solid;
[0060] (2) Synthesis of quaternary ammonium glycogen
[0061] Weigh 2.0 g of the amino glycogen prepared in step (1) and dissolve it in 50 mL of deionized water, dissolve it under magnetic stirring at 60° C., and adjust the pH to 8-9 with NaOH solution to obtain an amino glycogen solution;
[0062] 2.0 g of 2,3-epoxypropyltrimethylammonium chloride was added to the amino glycogen solution, and the mixture was stirred at a constant temperature of 60° C. for 6 h. After the reaction was completed, the solution was dialyzed for 3 days to remove unreacted quaternary ammonium salt, and then the dialyzate was freeze-dried to obtain quaternary ammonium glycogen solid.
[0063] Characterization of Glycogen Derivatives
[0064] 1. Figure 1 The freeze-dried solid products of (A) aminated glycogen and (B) quaternized glycogen are shown; according to calculation, the degree of substitution of the amino group on the aminated glycogen in Example 1 is 22.6%; the degree of substitution of the quaternary ammonium salt on the quaternized glycogen is 14.6%.
[0065] 2. The amino glycogen and quaternary ammonium glycogen synthesized in Example 1 were subjected to infrared spectroscopy (FTIR) and nuclear magnetic resonance spectroscopy ( 1 H-NMR), particle size, Zeta potential and micromorphology characterization.
[0066] Figure 2 A in the figure is the infrared spectra of glycogen, amino glycogen and quaternary ammonium salt glycogen. It can be seen that compared with glycogen, amino glycogen has a wavelength of 1695 cm -1 A new absorption peak appeared at 1536 cm-1, which was attributed to the carbonyl (C=O) stretching vibration absorption peak of the amide bond of ethylenediamine coupled to glycogen through CDI. In addition, the amino glycogen had a peak at 1536 cm-1. -1 、1260cm -1 There are also strong characteristic absorption peaks at 1450cm, which are the deformation vibration absorption peak of -NH- and the stretching vibration absorption peak of -CN-, indicating that the synthesis of amino glycogen is successful. -1 A new absorption peak appeared at , which was attributed to the deformation vibration absorption peak of the methyl group (-CH3) on the quaternary ammonium salt, indicating that the quaternary ammonium glycogen was successfully synthesized.
[0067] Figure 2 B is the NMR of glycogen, amino glycogen and quaternary ammonium glycogen. 1 From the H-NMR spectrum, it can be seen that compared with glycogen, the amino glycogen has a new absorption peak at 2.8ppm, which is attributed to the methylene structure on ethylenediamine; the quaternary ammonium glycogen has new absorption peaks at 4.3ppm and 3.1ppm. The 4.3ppm is the proton absorption peak of the methyne connected to the hydroxyl group in the quaternary ammonium salt, and the 3.1ppm is the proton absorption peak of the three methyl groups connected to nitrogen in the quaternary ammonium salt group, thus confirming the final product of the quaternary ammonium glycogen.
[0068] Table 1 shows the particle size and potential of glycogen, aminated glycogen and quaternary ammonium salt glycogen. The results show that amination significantly increases the particle size of glycogen, and after further quaternary ammonium salt treatment, the particle size slightly decreases. Glycogen itself has a small amount of negative charge. After coupling with ethylenediamine to form aminated glycogen, its Zeta potential changes from negative to positive. After quaternary ammonium salt treatment, its positive charge is significantly enhanced; the trend of Zeta potential changes shows that the gradual modification of glycogen is successful, and the quaternary ammonium salt modification makes glycogen have strong positive charge.
[0069] Table 1 Particle size and potential of glycogen, amino glycogen and quaternary ammonium salt glycogen
[0070]
[0071]
[0072] Figure 3 This is a transmission electron microscope image of quaternary ammonium glycogen. Through observation, it is found that the shape of the quaternary ammonium glycogen is similar to a sphere, and the particles are evenly dispersed with almost no agglomeration, basically maintaining a dendritic nanosphere structure.
[0073] 3. Test the antibacterial activity of the quaternary ammonium salt glycogen synthesized in Example 1
[0074] The quaternary ammonium salt glycogen was diluted to different concentrations by the two-fold dilution method and added to the 96-well plate one by one. Then, bacterial solution was added to the well plate to make the final bacterial concentration of 1×10 6 CFU / mL, after adding the sample, place the 96-well plate in a 37°C constant temperature biochemical incubator for 18 hours, and then use an ELISA reader to measure the absorbance of the sample plate at 600nm. Set the pure bacterial solution as the positive control and the pure quaternary ammonium salt glycogen solution as the negative control. The antibacterial rate calculation formula is as follows, where OD is the absorbance:
[0075]
[0076] The inhibition rate curve was drawn and the half minimum inhibitory concentration (MIC) of quaternary ammonium salt glycogen was calculated by regression using SPSS software. 50 ), the results showed that the MIC of quaternary ammonium glycogen against Staphylococcus aureus 50 The MIC of Escherichia coli is 2.62 mg / mL. 50 It is 44.12 mg / mL; the antibacterial effect of quaternary ammonium glycogen on Staphylococcus aureus is significantly stronger than that on Escherichia coli.
[0077] Example 2
[0078] The only difference from Example 1 is that the amount of 2,3-epoxypropyltrimethylammonium chloride in step (2) is adjusted to 1 g, 3 g, and 4 g, respectively, and the degree of substitution of the quaternary ammonium salt on the prepared quaternary ammonium glycogen is 6.7%, 20.9%, and 26.8%, respectively.
[0079] The quaternary ammonium glycogen prepared as above was subjected to an antibacterial test. The results showed that the antibacterial property of the quaternary ammonium glycogen became stronger with the increase of the degree of quaternary ammonium substitution. However, when the degree of quaternary ammonium substitution was higher than 22.6% of the degree of amination in the first step, the number of free amino groups was insufficient to meet the cross-linking of the quaternary ammonium glycogen and gelatin, and thus a composite hydrogel could not be formed. When the degree of quaternary ammonium substitution was lower than 10%, the antibacterial effect of the composite hydrogel was not ideal.
[0080] Example 3
[0081] A method for preparing a quaternary ammonium salt glycogen-gelatin composite antibacterial hydrogel, the method comprising the following steps:
[0082] Gelatin and the quaternary ammonium glycogen prepared in Example 1 were dissolved in ultrapure water at 40° C. (the mass concentration of gelatin was 10%, and the mass concentration of quaternary ammonium glycogen was 2.5%), mixed evenly, and bubbles were removed by ultrasound or centrifugation. The mixture was then poured into a mold and refrigerated at 4° C. to form the gel. The formed gel was then transferred into an EDC / NHS solution (the pH of the solution was adjusted to 4-6, the EDC concentration was 2 mg / mL, and the NHS concentration was 0.6 mg / mL) and soaked for 24 h at 4° C. for cross-linking reaction. The cross-linked gel was transferred into a PBS solution (pH 7.4), soaked overnight, and washed several times to obtain a quaternary ammonium glycogen-gelatin composite hydrogel. Fig. 9 A flow chart for preparation.
[0083] Example 4
[0084] The only difference from Example 3 is that the amount of quaternary ammonium glycogen added is adjusted to make its mass concentration in the solution 1% and 5%, respectively, and other conditions remain unchanged to prepare quaternary ammonium glycogen-gelatin composite hydrogel.
[0085] Comparative Example 1
[0086] The only difference from Example 3 is that the addition of quaternary ammonium salt glycogen is omitted, and other conditions remain unchanged to prepare a simple gelatin hydrogel.
[0087] Comparative Example 2
[0088] The only difference from Example 3 is that the quaternary ammonium salt glycogen in Example 3 is replaced by an equal amount of its precursor product, amino glycogen, and other conditions remain unchanged to prepare the amino glycogen-gelatin composite hydrogel.
[0089] Hydrogel performance determination
[0090] 1. Hydrogel appearance
[0091] Figure 4 The appearance morphology of the hydrogels prepared in Example 3 and Comparative Examples 1 and 2 is shown in Figure 2. By comparison, it is found that the gelatin hydrogel prepared in Comparative Example 1 is a colorless transparent solid; the amino-glycogen-gelatin composite hydrogel prepared in Comparative Example 2 is a milky white solid; and the quaternary ammonium-salted glycogen-gelatin composite hydrogel prepared in Example 3 is a translucent solid with gloss.
[0092] 2. Mechanical properties testing of hydrogel
[0093] At room temperature, the hydrogel (21-22 mm in diameter and 7-8 mm in height) was placed between a weighing sensor (50 kgf) with a circular metal clamp on a universal testing machine. The distance between the two clamps was adjusted until the upper clamp just touched the upper surface of the gel. The sample was then compressed at a speed of 1 mm / min until it broke, and a stress-strain curve was plotted based on the test data.
[0094] The mechanical properties of the hydrogels prepared in Example 3 and Comparative Examples 1 and 2 were measured. Figure 5 A in the middle is the stress-strain curve of the hydrogel. The stress gradually increases with the increase of strain. The stress-strain curve of the gelatin hydrogel increases slowly, while the stress-strain curves of the amino glycogen-gelatin composite hydrogel and the quaternary ammonium glycogen-gelatin composite hydrogel increase significantly.
[0095] Table 2 shows the fracture stress, fracture strain and compression modulus of the hydrogel. The results show that the fracture stress and compression modulus of the amino glycogen-gelatin composite hydrogel and the quaternary ammonium glycogen-gelatin composite hydrogel are significantly higher than those of the gelatin hydrogel.
[0096] Table 2 Fracture stress, fracture strain and compression modulus of hydrogel
[0097]
[0098] 3. Determination of swelling properties of hydrogel
[0099] The freeze-dried hydrogel was weighed and then completely immersed in room temperature PBS solution (pH 7.4). The samples were taken out at different time points and the excess water on the surface was removed, and then the weight of the samples was immediately measured and recorded. The swelling ratio (SR) was calculated as:
[0100]
[0101] Where W0 is the original weight of the freeze-dried hydrogel, and W1 is the weight of the sample after being immersed in PBS solution for a certain period of time.
[0102] The swelling properties of the hydrogels prepared in Example 3 and Comparative Examples 1 and 2 were measured. The results are as follows: Figure 5 As shown in Figure B, as time goes by, the weight of the hydrogel gradually increases and the swelling rate gradually increases; as the swelling rate of the hydrogel increases, the weight gain of the sample gradually decreases, the swelling rate change curve tends to be stable, and the hydrogel gradually absorbs water to saturation. At the same time point, the swelling rate of the gelatin hydrogel is the largest, followed by the amino glycogen-gelatin composite hydrogel, and the swelling rate of the quaternary ammonium salt glycogen-gelatin composite hydrogel is the smallest.
[0103] 4. Degradation performance of hydrogel
[0104] The in vitro degradability of the hydrogel was evaluated in PBS solution (pH 7.4) and PBS solution containing type I collagenase (1U / mL); the freeze-dried hydrogel was completely immersed in the PBS solution or enzyme solution and oscillated at 37°C and 100r / min for 6h, 12h, 24h, and 48h, respectively, centrifuged, the liquid was removed, the precipitate was washed, and then the precipitate was freeze-dried, weighed, and recorded. The degradation rate (BR) is calculated as:
[0105]
[0106] Where W0 is the original weight of the freeze-dried hydrogel, and W2 is the weight of the sample taken out and freeze-dried at a specific time.
[0107] The hydrogels prepared in Example 3 and Comparative Examples 1 and 2 were subjected to a degradation test.
[0108] In PBS solution: Figure 5 As shown in C, the degradation rate of the gel gradually increased with the increase of time; at the same time point, the degradation trends of the three gels were: gelatin hydrogel > quaternary ammonium glycogen-gelatin composite hydrogel > amino glycogen-gelatin composite hydrogel. The gelatin hydrogel degraded faster, and its degradation rate exceeded 90% at 48h; the degradation rate of quaternary ammonium glycogen-gelatin composite hydrogel was moderate, and its degradation rate reached 73.4% at 48h; the amino glycogen-gelatin composite hydrogel degraded relatively slowly, and its degradation rate was only 33.5% at 48h.
[0109] The gel was rapidly degraded in the collagenase solution, with the degradation rate reaching over 90% in 6 hours and 100% in 12 hours.
[0110] 5. Microscopic morphology observation of hydrogel
[0111] Figure 6 This is a scanning electron microscope image of the quaternary ammonium glycogen-gelatin composite hydrogel. The hydrogel has a connected network structure with a large pore size. There are round granular substances attached to the inner wall of the hydrogel. Judging from the size, they are quaternary ammonium glycogen nanoparticles, indicating that the quaternary ammonium glycogen is successfully cross-linked to the gelatin skeleton.
[0112] 6. Antibacterial test of hydrogel
[0113] 100 mg of amino glycogen-gelatin composite hydrogel and quaternary ammonium glycogen-gelatin composite hydrogel blocks after freeze-drying in Comparative Example 2 and Example 3 were weighed and sterilized under ultraviolet light overnight. Then, the blocks were immersed in sterile PBS solution to allow the gel to reach swelling equilibrium. The gels were transferred into 1 mL of Staphylococcus aureus or Escherichia coli bacterial suspension (1×10 6CFU / mL) were co-cultured at 37°C for 24 h, and then the number of viable bacteria was determined by plate count method. Figure 7 As shown in A:
[0114] Figure 7 A in the figure is the antibacterial rate of 2.5% amino glycogen-10% gelatin composite hydrogel and 2.5% quaternary ammonium glycogen-10% gelatin composite hydrogel. It can be seen that the antibacterial effect of quaternary ammonium glycogen-gelatin composite hydrogel is better than that of amino glycogen-gelatin composite hydrogel. The antibacterial rate of quaternary ammonium glycogen-gelatin composite hydrogel against Staphylococcus aureus reaches 97%, and the antibacterial rate against Escherichia coli reaches 50%, indicating that quaternary ammonium glycogen-gelatin composite hydrogel has good antibacterial effect.
[0115] The antibacterial activity of the 1% quaternary ammonium glycogen-10% gelatin composite hydrogel, 2.5% quaternary ammonium glycogen-10% gelatin composite hydrogel, and 5% quaternary ammonium glycogen-10% gelatin composite hydrogel prepared in Example 3 and Example 4 was tested. The results are as follows: Figure 7 As shown in B:
[0116] from Figure 7 From the data of B, it can be seen that with the increase of the amount of quaternary ammonium glycogen added, the antibacterial effect of the prepared quaternary ammonium glycogen-gelatin composite hydrogel is enhanced. When the addition amount of quaternary ammonium glycogen is 2.5%, the antibacterial rate of the prepared composite hydrogel against Staphylococcus aureus can reach 97%.
[0117] 7. Cytotoxicity test of hydrogel
[0118] Weigh 100 mg of the amino glycogen-gelatin composite hydrogel and quaternary ammonium glycogen-gelatin composite hydrogel after freeze-drying in Comparative Example 2 and Example 3, sterilize them by irradiation under ultraviolet light overnight, and then soak them in 4 mL of cell culture medium, extract them in a constant temperature shaker at 37°C and 100 r / min for 24 hours, collect the extract and filter it through a 0.22 μm filter membrane for later use. Mouse fibroblasts NIH-3T3 were co-cultured with the extract at 37°C and 5% CO2 for 24 hours and 48 hours, and then the cytotoxicity of the gel extract was determined by the MTT method.
[0119] The results are as follows Figure 8 As shown in A, at 24h, the cell survival rate of the quaternary ammonium glycogen-gelatin composite hydrogel was greater than 90%; at 48h, the cell survival rate of the quaternary ammonium glycogen-gelatin composite hydrogel was greater than 75%. This indicates that the quaternary ammonium glycogen-gelatin composite hydrogel has low cytotoxicity and good safety. By comparison, the cytotoxicity of the amino-glycogen-gelatin composite hydrogel is higher than that of the quaternary ammonium glycogen-gelatin composite hydrogel.
[0120] 8. Hemolysis test of hydrogel
[0121] Take mouse blood, separate red blood cells by centrifugation, wash with saline 5 times until the supernatant is clear, and resuspend the red blood cells with saline to prepare a suspension. Soak 50 mg of freeze-dried gel in Example 3 and Comparative Examples 1 and 2 in 1 mL of 1% red blood cell suspension, incubate in a 37°C water bath for 4 hours, centrifuge, and collect the supernatant. The absorbance of the supernatant at 540 nm was detected by an ELISA instrument. Use saline as a negative control (0% hemolysis) and pure water as a positive control (100% hemolysis). Calculate the hemolysis rate according to the following formula, where OD is the absorbance:
[0122]
[0123] Hemolysis rate exceeding 5% is considered hemolysis. Figure 8 As shown in B, the hemolysis rates of gelatin hydrogel, amino glycogen-gelatin composite hydrogel, and quaternary ammonium glycogen-gelatin composite hydrogel were all lower than 5%, and no hemolysis was observed in the supernatant, indicating that the three gels would not cause swelling of red blood cells and had good blood compatibility.
Claims
1. A method for preparing a quaternary ammonium salt glycogen-gelatin composite antibacterial hydrogel, characterized in that: The method comprises: dissolving gelatin and quaternary ammonium salt glycogen in ultrapure water at a mass ratio of 10:2-5, mixing evenly, removing bubbles, pouring into a mold, refrigerating at 0-4°C for molding, then transferring the molded gel into a crosslinker solution for immersion to perform a crosslinking reaction; transferring the crosslinked gel into a PBS solution, immersing overnight, and washing to obtain a quaternary ammonium salt glycogen-gelatin composite hydrogel; The preparation method of the quaternary ammonium salt glycogen comprises the following steps: (1) Synthesis of aminoglycogen Dissolve glycogen in dimethyl sulfoxide, then add N,N-carbonyldiimidazole to activate at 35-40°C for 1-2 hours to obtain a reaction solution; then dissolve ethylenediamine in dimethyl sulfoxide to form an ethylenediamine solution; under nitrogen protection, slowly add the ethylenediamine solution to the reaction solution through a syringe, and react at room temperature for 18-24 hours; after the reaction, dialyze and freeze-dry to obtain amino glycogen; (2) Synthesis of quaternary ammonium glycogen The aminated glycogen prepared in step (1) is dissolved in deionized water, and the pH is adjusted to 8-9 with a NaOH solution to obtain an aminated glycogen solution; a quaternary ammonium salt is added to the aminated glycogen solution, and the solution is stirred at a constant temperature of 50-60° C. to react, and after the reaction is completed, the solution is dialyzed and freeze-dried to obtain a quaternary ammonium salt glycogen; The mass ratio of the quaternary ammonium salt to the amino glycogen is 2 to 3:
2.
2. The method according to claim 1, characterized in that The quaternary ammonium salt in step (2) includes one or more of 2,3-epoxypropyltrimethylammonium chloride, tributylmethylammonium chloride, dodecyltrimethylammonium chloride, and hexadecyltrimethylammonium bromide.
3. The method according to claim 1, characterized in that The cross-linking agent solution includes one or more of EDC / NHS, genipin, and glutaraldehyde solution.
4. The method according to claim 1, characterized in that The pH of the cross-linking agent solution is 4 to 6; the cross-linking reaction time is 24 to 36 hours.
5. The quaternary ammonium salt glycogen-gelatin composite antibacterial hydrogel prepared by the method according to any one of claims 1 to 4.
6. Use of the quaternary ammonium salt glycogen-gelatin composite antibacterial hydrogel according to claim 5 in the preparation of pharmaceutical products.
Citation Information
Patent Citations
Collagen-based natural polymer hydrogel and preparation method thereof
CN110746516A
Application of polysaccharide quaternary ammonium salt to delivery of nucleic acid and proteins
CN111658784A